INCONSISTENCY OF MARKET LAWS IN PRICE CHANGES AND PRICE-FORMING ATTRACTOR - V. A. Chernov (Финансы: теория и практика, 2018)
The article critically examines the most frequently used in the scientific community the fundamental laws of price formation in a market economy. The author also reveals the incompleteness and lack of complexity in the interpretation of the Marxist direction of the labor theory of value by the subjects of the state economy of the Soviet period. New questions about the role of prices in global market processes, paradigms and definitions of pricing arise in the ongoing radical changes in geo-economics.In the complex interconnection to explore the role, importance, degree of dominance and signs of dominance of the most important basic laws of economic development and factors in the formation and change of prices in the dialectical relationship with changing conditions.The main method of research is the dialectical approach by which the author demonstrates on models the action, interaction, mutual influence of the fundamental laws of the market and the conditions underlying changes in market conditions and, consequently, prices. The fundamental components of the price allocated by the author are investigated as categorical oppositions.The author identifies financial and marketing components in the concept of price, reveals and substantiates the features and conditions that determine the predominance of one of these components. The article shows how under the influence of the laws of the market at different stages of the product’s life cycle in the changing of the entropy of prices is established a vibrational mode associated with the center of swing of the pendulum.Established a legitimate regime of prices’ entropy as the resultant of the interests of the parts of the converging it, determine the trajectory of price fluctuations and gradually comply the neighboring modes (transients) with the most common key law of pricing. To this conclusion, the author comes, exploring the interaction of various laws in the market processes of recent decades.